2004
DOI: 10.3171/spi.2004.1.1.0090
|View full text |Cite
|
Sign up to set email alerts
|

The use of bone morphogenetic protein—6 gene therapy for percutaneous spinal fusion in rabbits

Abstract: The results of this study show that an anatomically precise fusion can be accomplished by percutaneous administration of gene therapy. The next step in these studies will be extension of the technique to nonhuman primates and eventually to human clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…[16][17][18][19] We previously demonstrated that MSCs overexpressing a BMP gene could be effectively used to induce spine fusion in a mouse model. 20,21 The BMP gene can be introduced into a cell in a variety of ways, including viral 22,23 and nonviral methods. 21,24 MSCs can be isolated from various adult tissues, such as bone marrow and adipose tissue, 25 following common procedures such as liposuction.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] We previously demonstrated that MSCs overexpressing a BMP gene could be effectively used to induce spine fusion in a mouse model. 20,21 The BMP gene can be introduced into a cell in a variety of ways, including viral 22,23 and nonviral methods. 21,24 MSCs can be isolated from various adult tissues, such as bone marrow and adipose tissue, 25 following common procedures such as liposuction.…”
Section: Introductionmentioning
confidence: 99%
“…Adenoviral BMP-6 vector construct showed induction of local bone tissue deposition and fusion after multiple level percutaneous injections in the spine of rabbits (12). the same study also demonstrates that BMP-6 gene therapy can induce bone formation in immunocompetent animals, even when administered with an antigenic vector.…”
Section: Mitogensmentioning
confidence: 48%
“…The genetic modification of MSCs by transducing them with genes capable of regulating the expression and secretion of osteoinductive factors has been employed in an attempt to promote bone formation in spinal arthrodesis and to overcome the complications associated with the local delivery of rhBMPs. Gene delivery is achieved by using a vector (viral or nonviral) through either an in vivo approach, involving the direct introduction of the target gene-containing vector to the fusion site, as illustrated by research from Helm's group [93][94][95], or an ex vivo approach, involving the harvesting and optional culture expansion of MSCs prior to gene transduction.The transduction of BMSCs with genes encoding BMP-2 [96][97][98][99][100], BMP-4 [101], BMP-6 [94], BMP-7 [102], BMP-9 [93,103], LIM mineralization protein [104] and the osteoinductive factor Nell-1 [105] have all successfully been shown to induce spinal fusion in small animal studies. In addition, the transduction of adipose tissue-derived MSCs with BMP-expressing genes has also been shown to promote bone formation in both small and large animal spinal models [106][107][108] with spinal fusion rates comparable to those achieved with genetically modified BMSCs [109].…”
Section: Tissue Engineering Strategiesmentioning
confidence: 99%